Preclinical evaluation of thermosensitive poly(N-(2-hydroxypropyl) methacrylamide mono/dilactate)-grafted liposomes for cancer thermochemotherapy - van Elk, Merel; van den Dikkenberg, Joep B; Storm, Gert; Hennink, Wim E; Vermonden, Tina; Heger, Michal (Elsevier BV, 2018)
Thermosensitive liposomes grafted with cholesterol-conjugated poly(N-(2-hydroxypropyl) methacrylamide mono/dilactate) (chol-pHPMAlac) have been developed for heat-induced release of doxorubicin (DOX). These liposomes release DOX completely during mild hyperthermia, but their interaction with blood cells and cancer cells has not been studied. Following intravenous administration, liposomes may interact with plasma proteins and various types of cells (e.g., endothelial cells, platelets, and macrophages), which would reduce their disposition in the tumor stroma. Interaction between liposomes and platelets may further cause platelet activation and thrombosis, which could lead to vascular occlusion and thromboembolic complications. The aim was to investigate DOX release kinetics in the presence of serum, stability, in vitro uptake by and toxicity to cancer cells and somatic cells, and platelet activating potential of the chol-pHPMAlac liposomes. DOX release was determined spectrofluorometrically. Liposome stability was determined in buffer and serum by dynamic light scattering and nanoparticle tracking analysis. Association with/uptake by and toxicity of empty liposomes to AML-12, HepG2 (both hepatocyte-derived cancer cells), RAW 264.7 (macrophages), and HUVEC (endothelial) cells was assayed in vitro. Platelet activation was determined by analysis of P-selectin expression and fibrinogen binding. DOPE:EPC liposomes (diameter = 135 nm) grafted with 5% chol-pHPMAlac (cloud point (CP) = 16 °C; Mn = 8.5 kDa) released less than 10% DOX at 37 °C in 30 min, whereas complete release took place at 47 °C or higher within 10 min. The size of these liposomes remained stable in buffer and serum during 24 h at 37 °C. Fluorescently labeled but DOX-lacking chol-pHPMAlac-liposomes exhibited poor association with/uptake by all cells under investigation, were not cytotoxic, and did not activate platelets in both buffered solution and whole blood. In conclusion, thermosensitive chol-pHPMAlac-grafted liposomes rapidly release DOX during mild hyperthermia. The liposomes are stable in a physiological milieu, are not taken up by cells that are encountered in an in vivo setting, and are non-antagonistic towards platelets. Chol-pHPMAlac-grafted liposomes are therefore good candidates for DOX delivery to tumors and temperature-triggered release in tumor stroma.
Keywords: Targeted drug delivery; Oncology; Heat-triggered drug release; Tumor stroma; Doxorubicin; Hyperthermia; Taverne; SDG 3 - Good Health and Well-being